Peer Effects and Incentives - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2014)
In a multi-agent setting, individuals often compare own performance with that of their peers. These comparisons influence agents' incentives and lead to a noncooperative game, even if the agents have to complete independent tasks. I show that depending on the interplay of the peer effects, agents' efforts are either strategic complements or strategic substitutes. I solve for the optimal monetary incentives that complement the peer effects and show that the principal prefers sequential effort choices of the agents to choosing efforts simultaneously.
Keywords: C72; D03; D86; 330; externalities; moral hazard; other-regarding preferences